Process Writing in the Context of Teaching English as a Foreign Language - Yamalee, Eason (Ratchaphruek Journal, 2020)
This article focuses on providing knowledge and lesson for readers about teaching English in process writing. This teaching approach emphasizes each step of writing, which contradicts with teaching writing by a product-oriented approach. The article also points out important components that the English writing instructors especially at tertiary level must pay attention when they want to apply this approach. They include interaction and feedback in terms of teacher written feedback, teacher-student conferencing, and peer feedback. Though providing feedback is a small part, it enhances anyone who is interested in studying process writing to understand the way to teach writing fruitfully. Feedback emerges because the students have to write multiple drafts, which are provided comments by the instructor in terms of content, organization, and grammar. When learners and instructor understand feedback, the students can improve their writing, and their writing tasks are ready to be evaluated as the final draft. However, this article only provides some perspectives for both instructors and learners to realize and understand various types of providing feedback in order to adapt them in the appropriate context of teaching, but it cannot indicate the best way of providing feedback. Therefore, the instructors have to understand the context of their students so that they can adapt the feedback that suits their context.